THE FREE EXPRESSION OF FREEDOM IN THE FACE OF ITS EXCESSES - de Almeida Silva , Alifer (Revista Gênero e Interdisciplinaridade, 2022)
This article analyzes in a contextualized way the right to freedom of expression exercised by people. Specifically, it is intended to demonstrate part of the breadth of the right to freedom of expression without romanticizing it, it is a fundamental right for life in society, the Federal Constitution (1988) and international treaties assert this. However, it is not an absolute right, since starting from the generic and logical premise of “your right ends when the rights of others begin” one realizes the importance of protecting this right and exercising it responsibly, because currently freedom, in general, prevails in Brazil due to the Federal Constitution (1988) prioritizing it, in fact it is a country that has just emerged from a dictatorial regime, and a regime of this nature has the limiting nature of the freedom to express oneself, while the democratic regime promotes this freedom.